(untitled) (Prithvi Academic Journal, 2026)
Self-medication (SM) is a growing global phenomenon especially prevalent in low-income communities where access to formal healthcare is limited. Unauthorized use of medication poses serious risks, including drug resistance, harmful side effects, and delayed access to professional medical care. This study explored the prevalence, causes, and consequences of SM among low-income households in Pokhara Valley. The researchers surveyed 150 households across seven randomly selected slums using structured questionnaires and analyzed the data using multiple regression with heteroscedasticity error correction model. The investigation revealed an 82.3% SM prevalence rate primarily driven by cost and time savings, with 24% of households reporting side effects such as allergies. The findings indicate that the frequency of SM is significantly associated with education levels, household size, and the perceived ease of treatment. These results underscore the urgent need for targeted public awareness s campaigns and improved access to formal medical facilities for marginalized populations.